ANALISIS KINERJA KEUANGAN BERDASARKAN ECONOMIC VALUE ADDED (EVA) DAN FINANCIAL VALUE ADDED (FVA) (STUDI KASUS PADA PT. NIPPON INDOSARI CORPINDO TBK. TAHUN 2014-2018) - Mohamad, Nangsi; Amali, Lanto Miriatin; Dungga, Meriyana Franssisca (Universitas Ahmad Dahlan, 2020)
Analysis of Financial Performance based on Economic Value Added (EVA) and Financial Value Added (FVA) (Case Study at PT. Nippon Indosari Corpindo Tbk in 2014-2018). Bachelorâ€™s Degree Program in Management, Faculty of Economics, State University of Gorontalo. The principal sepervisior is Lanto Miriatin Amali, S. Sos., M.Si., and the co-supervisor is Meriyana Frsansissca Dungga, SE, MM.Â The research objective was to find out the financial performance of company based on analysis Economic Value Added (EVA) and Financial Value Added (FVA) from 2014 to 2018 at PT. Nippon Indosari Corpindo Tbk. The research data were obtained through financial statement in Indonesia Stock Exchange in form of companyâ€™s annual statement. The research data were secondary data. The research method used quantitative descriptive. The research sample focused on PT. Nippon Indosari Corpindo Tbk at Indonesia Stock Exchange (IDX). The research finding indicated that the result of calculation from economic value added (EVA) and Financial Value Added (FVA) at PT. Nippon Indosari Corindo Tbk listed in Indonesia Stock Exchange (IDX) fluctuated or limit of economic value added and limit of financial value added were dynamic expriencing movement although the condition of value was dynamic (up-down). Yet the average value of both was > 0 (positive) so that it was assumed to have been able to create economic value added and financial value added.